2019
DOI: 10.1128/jvi.02077-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Novel Fc Gamma-Binding Glycoprotein in Rhesus Cytomegalovirus

Abstract: Receptors recognizing the Fc part of immunoglobulin G (FcγRs) are key determinants in antibody-mediated immune responses. Members of the Herpesviridae interfere with this immune regulatory network by expressing viral FcγRs (vFcγRs). Human cytomegalovirus (HCMV) encodes four distinct vFcγRs that differ with respect to their IgG subtype specificity and their impact on antibody-mediated immune function in vitro. The impact of vFcγRs on HCMV pathogenesis and immunomodulation in vivo is not known. The closest evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…However, it is already known that HCMV vFcγRs also antagonize activation of FcγRIIA (CD32) and FcγRI (CD64) (Corrales-Aguilar, Trilling, et al, 2014) and we also consistently observed antagonization of the only inhibitory FcγR, FcγRIIB (unpublished observation). Similarly, we could recently show antagonization of all canonical Rhesus FcγRs I, IIA, IIB and III by the RhCMV encoded vFcγR gpRH05 ( RL11 gene family) (Kolb et al, 2019). Taken together with the data shown in this study that the underlying mechanism seems to be related between FcγRs IIA/B and III, we also speculate that more Fcγ binding host factors might be antagonized by similar mechanisms involving vFcγRs.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, it is already known that HCMV vFcγRs also antagonize activation of FcγRIIA (CD32) and FcγRI (CD64) (Corrales-Aguilar, Trilling, et al, 2014) and we also consistently observed antagonization of the only inhibitory FcγR, FcγRIIB (unpublished observation). Similarly, we could recently show antagonization of all canonical Rhesus FcγRs I, IIA, IIB and III by the RhCMV encoded vFcγR gpRH05 ( RL11 gene family) (Kolb et al, 2019). Taken together with the data shown in this study that the underlying mechanism seems to be related between FcγRs IIA/B and III, we also speculate that more Fcγ binding host factors might be antagonized by similar mechanisms involving vFcγRs.…”
Section: Discussionmentioning
confidence: 58%
“…S4). Similar membrane-distal YXXΦ motifs also exist in the cytosolic domains of HCMV encoded gpRL13 and gB, making the di-leucine motif found in gp34 unique among other surface-resident glycoproteins expressed by HCMV and all other vFcγRs known in CMV family members including RhCMV and MCMV(Kolb et al, 2019; Thale, Lucin, Schneider, Eggers, & Koszinowski, 1994). It remains to be explored as to what the further consequences of this seemingly unique internalization route is.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, it has also been demonstrated that rhesus CMV (RhCMV) Rh05 encodes a homolog of HCMV gp34 and mediates the IgG-dependent activation of rhesus FcγRs. 17 Our study has a limitation in the lack of demonstration of IgG-binding capacity of, or inhibition of, FcγR activation by GP119.1 in infected F I G U R E 5 Localization of GP119.1 expressed in the GPCMV-infected cells. At 90 h after infection of GPL cells with f119 or d119, the cells were stained with anti-DDDDK antibody against the FLAG tag, and fluorescent images were captured by a confocal microscope.…”
Section: Lack Of Gp1191 Had No Effect On Viral Growth In Cell Cultmentioning
confidence: 92%
“…Recombinant RhCMV clones were generated by en passant mutagenesis, as previously described for HCMV (65), and adapted by us for RhCMV (66). This technique allows the generation of fusion protein, have been described before (14,53).…”
Section: Bac Recombineering Using En Passant Homologous Recombinationmentioning
confidence: 99%